Molecular HDD logic for encrypted massive data storage - Guo, Bingjie; Chen, Xinhui; Chen, An; Wang, Jinxin; Xue, Wuhong; Wang, Tao; Wu, Zhixin; Zhong, Xiaolong; Zeng, Jianmin; Li, Jinjin; Li, Mao; Xu, Xiaohong; et al. (Nature communications, 2025)
Organic memories, with small dimension, fast speed and long retention features, are considered as promising candidates for massive data archiving. In order to satisfy the requirements for ultra-low power and high-security information storage, we design a conceptual molecular hard-disk (HDD) logic scheme that is capable to execute in-situ encryption of massive data in pW/bit power-consumption range. Beneficial from the coupled mechanism of counter-balanced redox reaction and local ion drifting, the basic HDD unit consisting of ~200 self-assembled Ru X LPH molecules in a monolayer (SAM) configuration undergoes unique conductance modulation with continuous, symmetric and low-power switching characteristics. 96-state memory performance, which allows 6-bit data storage and single-unit one-step XOR operation, is realized in the Ru X LPH SAM sample. Through single-unit XOR manipulation of the pixel information, in-situ bitwise encryption of the Mogao Grottoes mural images stored in the molecular HDD is demonstrated. Organic memory devices, with small dimension, fast speed and long retention are promising candidates for data archiving. Here, the authors present a molecular hard-disk logic scheme capable of executing in-situ encryption of data in pW/bit power-consumption range.